Epigenetic deregulated miR-375 contributes to the constitutive activation of JAK2/STAT signaling in myeloproliferative neoplasm. Issue 4 (April 2015) - Yin, Li-hui; Zheng, Xiao-qun; Li, Hai-ying; Bi, Lai-xi; Shi, Yi-fen; Ye, Ai-fang; Wu, Jian-bo; Gao, Shen-meng
Graphical abstract